Perception of Non-Muslim Accounting Students towards Sharia Accounting Courses at the University of Mataram - Melianta, Khusnul; Lenap, Indria Puspitasari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the perception of non-Muslim accounting students towards the Sharia Accounting course. This study uses a qualitative method with a transcendental phenomenological approach to determine the deepest awareness of non-Muslim accounting students regarding their perceptions of Sharia Accounting. Data collection was conducted by conducting direct interviews with five non-Muslim students majoring in Accounting at the University of Mataram. The results of the study indicate that the initial understanding of non-Muslim students considers Sharia Accounting as an exclusive course for Muslims, but through learning experiences, they begin to understand universal values ​​such as justice, transparency, and business ethics. The development of sharia financial institutions in Indonesia makes this material relevant to the world of work. Although the learning method is quite effective, additional approaches such as case studies and systematic modules are still needed.